(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In the article, the boundedness of vector-valued sublinear operators in grand variable Herz-Morrey spaces M K_ λ, p(·)^η (·), q), θ(R^n) are obtained. Then grand variable Herz-Morrey type Besov and Triebel-Lizorkin spaces are defined. We will also prove the equivalent quasi-norms by Peetre’s maximal operators in these spaces.